A prenyl pyrophosphate synthase gene from the zygomycete fungus, Gilbertella persicaria - Nagy, Gábor (ACTA BIOLOGICA SZEGEDIENSIS (Print), 2011)
In this study, a prenyl pyrophosphate synthase gene was cloned and characterized in the zygomycete fungus Gilbertella persicaria. The coding region of the isolated gene comprises a total of 1328 bp determining a 350 amino acids length putative protein and five introns (60, 65, 43, 59, and 48 bp in length) dispersed in the whole coding region. Based on the analysis of the nucleotide and the corresponding amino acid sequence, the gene encodes a farnezyl pyrophosphate synthase, and it was named as isoA. In a phylogeny inferred from amino acid sequences of fungal prenyl pyrophosphate synthases, the Gilbertella isoA proved to be the most closely related to that of Mucor circinelloides. Carotenoid composition of G. persicaria was also investigated: it produces B-carotene as the main carotenoid, but it also contains small amounts of B-cryptoxanthin, zeaxanthin and astaxanthin.